The involvement of peritoneal GATA6+ macrophages in the pathogenesis of endometriosis - Shi, Mingxin; MacLean, James A.; Hayashi, Kanako (Frontiers in Immunology, 2024)
Endometriosis is a chronic inflammatory disease that causes debilitating pelvic pain in women. Macrophages are considered to be key players in promoting disease progression, as abundant macrophages are present in ectopic lesions and elevated in the peritoneum. In the present study, we examined the role of GATA6 + peritoneal macrophages on endometriosisassociated hyperalgesia using mice with a specific myeloid deficiency of GATA6. Lesion induction induced the disappearance of TIM4 hi MHCII lo residential macrophages and the influx of increased Ly6C + monocytes and TIM4 lo MHCII hi macrophages. The recruitment of MHCII hi inflammatory macrophages was extensive in Mac Gata6 KO mice due to the severe disappearance of TIM4 hi MHCII lo residential macrophages. Ki67 expression confirmed GATA6-dependent proliferative ability, showing different proliferative phenotypes of TIM4 + residential macrophages in Gata6 f/f and Mac Gata6 KO mice. Peritoneal proinflammatory cytokines were elevated after lesion induction. When cytokine levels were compared between Gata6 f/f and Mac Gata6 KO mice, TNFα at day 21 in Gata6 f/f mice was higher than in Mac Gata6 KO mice.Lesion induction increased both abdominal and hind paw sensitivities. Gata6 f/f mice tended to show higher sensitivity in the abdomen after day 21. Elevated expression of TRPV1 and CGRP was observed in the dorsal root ganglia after ELL induction in Gata6 f/f mice until days 21 and 42, respectively. These results support that peritoneal GATA6 + macrophages are involved in the recruitment and reprogramming of monocyte-derived macrophages. The extensive recruitment of monocyte-derived macrophages in Mac Gata6 KO mice might protect against inflammatory stimuli during the resolution phase, whereas GATA6 deficiency did not affect lesion initiation and establishment at the acute phase of inflammation. GATA6 + residential macrophages act to sustain local inflammation in the peritoneum and sensitivities in the neurons, reflecting endometriosis-associated hyperalgesia.